Penerapan Metode Pembelajaran Al Qur’an Di Kecamatan Gadingrejo Kabupaten Pringsewu - Ifan Hanafi; Muhammad Akmansyah; Amiruddin (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
In the current condition, learning to read the Qur'an is very varied, because many methods are used to implement it. Therefore, with the development of the Qur'an learning methods that exist in the Gadingrejo community, the researchers want to know what methods are used in it, how it is applied and what makes the success of each method in implementing it to all students who are learning related to reading. Qur'an. For the research method used in the study, namely using qualitative research methods and the type of research using descriptive qualitative, for data collection using observation, documentation and interviews, while in analyzing the data using data reduction, data presentation and drawing conclusions and finally the research methodology to test the validity of the data using the data triangulation test. As for the results of the first research, the methods used in Gadingrejo District are the Turutan (Baghdadiyah), Iqro' and Yanbu' methods in the process of learning to read the Qur'an. While the implementation of each method has its own characteristics, for the follow-up method (Baghdadiyah), namely by spelling letter by letter, then Iqro' which emphasizes the active student learning method (CBSA), while the last method is the Yanbu' method, namely by learning quickly and precisely not spell. For its advantages, it is indeed a follow-up method to recognize the original letters, Iqro' is famous for being simple and yanbu using rosm usmany, narrated by Imam Hafs. For the supporting and inhibiting factors in the application of the Qur'an method, it starts from internal factors including the motivation of students, intelligence and morals of students, while from external factors starting from the infrastructure and the environment around the community.